RISIKOADFÆRD OG DET GODE LIV: Spørgsmål til en livsstil med øl, cigaretter og mangel på motion - Raffing, Rie; Pisinger, Charlotta (Tidsskriftet Antropologi, 2008)
This pilot study looks into the question of why some people continue a lifestyle of risk behaviour, knowing full well that this might cause them illness in the future. Risk behaviour in this study was defined by not meeting the recommendations from the Danish National Board of Health: Not to smoke, to keep a BMI lower than 25, to drink less than 14 (women) or 21 (men) standard drinks per week and to be physically active at least half an hour each day. Each interviewee failed to meet at least two of these recommendations and did not have plans to change his or her lifestyle. The aim of this study was to qualitatively investigate how four citizens from West Copenhagen, with high risk behaviour, regarded the concepts of health, illness and risk; the study also addresses the factors that would increase their motivation for lifestyle change. This study showed that the informants’ attitudes to risk behaviour were negotiated, created and maintained around the following themes which are part of a practical rationalism: “future”, “probability”, “it happens to others” and “luck”. The threat of illness caused by risk behaviour was expected to be the primary motivating factor for lifestyle change. The informants with high-risk behaviour had a short-term perspective that dominated their everyday lives. They didn’t expect to fall ill due to their risk behaviour, but if they did, they considered the disease to be the primary motivating factor for lifestyle change.